Performance Enhancement of State-of-the-Art Cryptography Algorithms in the Banking Sector - Surla, Govindu; Lakshmi, R. (2023 Third International Conference on Ubiquitous Computing and Intelligent Information Systems (ICUIS), 2023)
Data security is a complex subject in today's world that affects both data storage and data transmission. In recent months, we've seen a lot of cyber security attacks that have tampered with consumer privacy. These assaults simply smashed all the security algorithms and had an impact on user data's identity, confidentiality, authentication, integrity, and availability. One such technique is the use of cryptography to ensure data secrecy, authentication, integrity, availability, and identification. Encryption is the process of converting plaintext, or ordinary data, into something obscure or ciphertext using mathematical formulas or changes. Algorithms are the terms used to describe these mathematical operations or formulas utilized in encryption techniques. The data encryption techniques, including DES, BLOWFISH, RSA, SHA, EIGAMAL, TEA, and others, have been examined. Symmetric key encryption methods include DES and BLOWFISH. There are asymmetric key encryption algorithms such as RSA and SHA. To determine the best data encryption method many encryption algorithms have been analyzed and compared based on various characteristics.